(untitled) (Research, Society and Development, 2021)
This work aimed to study the CO2 flux in the environment and its relationship with the sky coverage, in search of a mathematical relationship between these variables. It was also aimed to propose an empirical model that correlates solar radiation with CO2 fluxes (and consequently photosynthesis and plant productivity). CO2 flux data were obtained from satellites, from two bases: the base “PML_V2” and the base “MODIS17A2H”. The gross daily production of carbon was related to diffuse solar radiation. The CO2 flux data obtained from the “PML_V2” program better fit the solar radiation data from Botucatu-SP. The data from the “MODIS17A2H” program needs further studies, especially in its parameterization, which involves elements of local vegetation. In the multivariate equation obtained to estimate the gross primary production of GPP as a function of diffuse solar radiation, the Kt value per month presented high performance values, with r = 0.88, MBE = -6.99% and RMSE = 16.70%.